Chamber Music Instruction: Reflections from Online Teaching during the COVID-19 Lockdown - Janyarayachon, Sethapong; Dilokkunanant, Komsun (Journal of Education Studies, Chulalongkorn University, 2025)
The COVID-19 pandemic led to lockdown measures worldwide, including in Thailand. As a result, the traditional approach to chamber music instruction at Princess Galyani Vadhana Institute of Music had to be adapted into an online format during the 2021 and 2022 academic years. This unprecedented situation prompted a reassessment of conventional chamber music teaching strategies and the development of an entirely new instructional plan to address the unique challenges of online delivery. Consequently, it became necessary to re-examine the expected learning outcomes to ensure that students could continue to develop chamber music skills through online instruction despite lockdown conditions. The revised approach combined traditional and innovative methods to create a more comprehensive and balanced model of chamber music instruction, while opening possibilities for reimagined post-pandemic teaching practices. This blended model enabled students to acquire broader skills than through onsite methods alone and helped them become more accomplished and versatile chamber musicians. This study presents an analysis of strategies for addressing challenges and leveraging opportunities arising from online chamber music instruction during the COVID-19 lockdown and proposes a conceptual framework for integrating the developed approaches into primarily face-to-face instruction.